If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6x = -2 Combine like terms: 8x + -6x = 2x 2x = -2 Solving 2x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = -1 Simplifying x = -1
| 28-(-8)-3=m | | x^2+x+0.5=0 | | 11d=11 | | X=-8+5x | | -12-25-32-(-9)=p | | -4-4=8-7x | | 15y=150 | | 14-.666666x=18 | | x+-24=10 | | 13.374x^2-258.431x+1724.415=0 | | -4x-5+x=4 | | -5(3q+9)=45 | | 15=.6n | | -4=4(6g-12)-2y | | 6-3x+2x=9x+26 | | .6x+22=28 | | -(4)(-2)= | | 3x-10=x+8 | | 3a-12b=x | | .5b=3 | | R=-6.25x^2+75x+1000 | | 0.55b=3 | | 3x-8=6x+8 | | -(10)= | | 14=5x-4x+8 | | .5x-29=-22 | | 8-3x=4+x | | 2p+22=-6p | | x+24=10 | | -(-9)= | | 32=0.6x+-34 | | (3w+5)(w+1)= |